An investigation of the effects of curcumin on iron overload, hepcidin level, and liver function in β‐thalassemia major patients: A double‐blind randomized controlled clinical trial - Mohammadi, Elahe; Tamaddoni, Ahmad; Qujeq, Durdi; Nasseri, Esmat; Zayeri, Farid; Zand, Hamid; Gholami, Mahdi; Mir, Seyed Mostafa (Phytotherapy research, 2018)
This study investigated the effects of curcumin, the active polyphenol in turmeric, on iron overload, hepcidin level, and liver function in β‐thalassemia major patients. This double‐blind randomized controlled clinical trial was conducted on 68 β‐thalassemia major patients. The subjects were randomly divided into 2 groups to receive either 500 mg curcumin capsules (total: 1,000 mg) twice daily or placebo for 12 weeks. Dietary intakes and biochemical variables including hemoglobin, transferrin saturation, total iron binding capacity, nontransferrin bound iron (NTBI), ferritin, hepcidin, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were assessed at the beginning and end of the trial. Curcumin significantly reduced serum levels of NTBI (2.83 ± 1.08 compared with 2.22 ± 0.97 μmol/L, p = .001), ALT (42.86 ± 11.15 compared with 40.60 ± 9.89 U/L, p = .018), and AST (49.45 ± 12.39 compared with 46.30 ± 10.85 U/L, p = .002) at the end of the study. Based on analysis of covariance, a significant decrease was also observed in levels of NTBI (2.22 ± 0.97 vs. 2.55 ± 0.94 μmol/L, p = .026), ALT (40.60 ± 9.89 vs. 45.01 ± 10.42 U/L, p = .004), and AST (46.30 ± 10.85 vs. 50.99 ± 9.36 U/L, p = .009) in curcumin group in comparison with placebo group. There were no significant changes in hepcidin and other variables in any of the 2 groups. Curcumin administration alleviated iron burden and liver dysfunction by reducing NTBI, ALT, and AST levels in patients with β‐thalassemia major.